Search for exclusive radiative decays of Υ{hooked}(1 S) and Υ{hooked}(2 S) mesons - Albrecht,H; Böckmann,P; Gläser,R; Harder,G; Krüger,A; Nippe,A; Reidenbach,M; Schäfer,M; Schmidt-Parzefall,W; Schröder,H; Schulz,HD; Sefkow,F; et al. (Zeitschrift Fur Physik C Particles and Fields, 1989)
Using the ARGUS detector at the DORIS II storage ring we have searched for radiative decays Υ(1 S)→γX, where X decays into two oppositely charged pions, kaons, or protons. Upper limits on branching fractions are presented. In the π+π- invariant mass region 290-570 MeV/c2 the upper limit obtained varies from 3 to 4.5×10-5. These values are lower than the theoretical prediction of about 5×10-5 for Higgs production, which includes perturbative QCD radiative corrections to the Wilczek formula and the estimate Br(H0→π+π-), accounting for Higgs coupling to gluons via heavy quark loops. Previous experimental results do not exclude the existence of a standard minimal Higgs in this mass region. © 1989 Springer-Verlag.